Fabrication and characterization of a high strength ultra-fine grained metal-matrix AA8006-B4C layered nanocomposite by a novel accumulative fold-forging (AFF) process. (5th November 2018) - Khodabakhshi, F.; Gerlich, A.P.; Worswick, M.
Abstract: In this study, a new manufacturing process, accumulative fold-forging (AFF), based on the severe plastic deformation (SPD) concept was implemented for fabrication of nanostructured metal-matrix nanocomposites. This process was accomplished at room temperature for up to 26 fold-forging steps with an intermediate annealing treatment at a temperature of 150 °C between the passes, and produces 67, 108, 864 layers to incorporate a ~10 vol% of boron carbide nanoparticles homogenously within the Al-Fe-Mn aluminum alloy matrix. The results indicate a structure is formed with well-bonded interfaces/inter-layers with uniformly dispersed precipitates and nanoparticles between them, leading to formation of an ultra-fine grain structure in the matrix with a mean grain size <50 nm and a dislocation density as high as ~8.1 ∗ 10 16  m −2 . As a result, an ultra-fine grained (~35 nm) AA8006-B4 C (34 nm, 10 vol%) layered metal-matrix nanocomposite was produced. The hardness of annealed Al-foil was ~30 HV which was enhanced by more than six times to a maximum amount of ~205.4 HV, corresponding to one of the highest reported hardness values for an aluminum based composite, due to the role of nano-layers, nano-grains, and nano-particles as the main strengthening mechanisms. Graphical abstract: Unlabelled Image Highlights: The novel AFF process was developed for fabrication of layered nanocomposites. A high fraction of B4 C nanoparticles (~10 vol %) was homogenously incorporated. A refined grain structure <50 nm with enhanced dislocation density was attained. The hardness was increased up to ~205.4 HV (more than six times higher).